(untitled) (Journal of School Administration Research and Development, 2022)
School-law enforcement partnerships benefit from well-written memorandums of understandings (MOUs) that have been collaboratively developed with input from school law enforcement agencies and school divisions. While many school-law enforcement partnerships report having MOUs, little is known about what information the MOUs provide. We conducted a content analysis of 73 MOUs from school-law enforcement partnerships in Virginia. We coded the MOUs to obtain information about MOU structure and format and the coverage of three topic areas: school resource officer (SRO) roles, SRO training, and SRO role in school discipline. Our analysis revealed most MOUs cover the three topic areas, but what the MOUs said about these topics varied tremendously. The findings suggest all those involved in MOU development might benefit from easily accessible, streamlined resources that outline what specific issues need to be addressed when creating MOUs and how to navigate nuanced discussions about the roles and training of SROs.